2020
DOI: 10.1016/j.virusres.2020.198137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remdesivir on patients with COVID-19: A network meta-analysis of randomized control trials

Abstract: Highlights We did network meta-analyses comparing clinical improvement of COVID-19 patients. We compared 5-day course vs. 10-day course of remdesivir vs standard care. Clinical improvement was higher in 5-day and 10-day course than standard care. Clinical improvement was higher in 5-day than 10-day remdesivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 5 publications
5
51
1
Order By: Relevance
“…But case-2 had hypoalbminemia on presentation. Case-1 and 2 patients had 4 and 6 treatment days with remdesivir respectively, with no improvement, in contrast to published trials in which remdesivir treatment course of 5 days had shown signi cant improvements [16,17]. Our second case patient received remdesivir after 4 days of presentation of COVID-19 symptoms, which is consistent with published literature reporting that the e cacy of remdesivir is higher in patients who received it within 10 days of symptoms presentation [18].…”
Section: Discussionsupporting
confidence: 86%
“…But case-2 had hypoalbminemia on presentation. Case-1 and 2 patients had 4 and 6 treatment days with remdesivir respectively, with no improvement, in contrast to published trials in which remdesivir treatment course of 5 days had shown signi cant improvements [16,17]. Our second case patient received remdesivir after 4 days of presentation of COVID-19 symptoms, which is consistent with published literature reporting that the e cacy of remdesivir is higher in patients who received it within 10 days of symptoms presentation [18].…”
Section: Discussionsupporting
confidence: 86%
“…The comparison of the remdesivir groups with the standard‐care group showed a significantly higher rate of improvements in clinical status (odds ratio [OR], 1.89; 95% confidence interval [CI], 1.40‐2.56; P < .001; and OR, 1.38; 95%CI, 1.15‐1.66; P < .001, for 5‐day and 10‐day remdesivir groups, respectively). Also, patients who received remdesivir for 5 days showed a better clinical improvement than the 10‐day remdesivir group (OR, 1.37; 95%CI, 1.01‐1.85; P = .041) 31 . However, this study could not consider further outcomes such as mortality and safety concerns.…”
Section: Remdesivir (I B‐r Us Food and Drug Administration Approved)mentioning
confidence: 84%
“… 27 Another meta-analysis with 76 articles using remdesivir revealed that further randomized controlled trials with larger sample sizes are required to identify the best candidate components that should comprise combined treatments for COVID-19. 28 …”
Section: Discussionmentioning
confidence: 99%